Obstructive sleep apnea in patients with diabetes less than 40 years of age. Issue 6 (November 2020) - Soontornrungsun, Benjawan; Khamsai, Sittichai; Sawunyavisuth, Bundit; Limpawattana, Panita; Chindaprasirt, Jarin; Senthong, Vichai; Chotmongkol, Verajit; Sawanyawisuth, Kittisak
Abstract: Background and aim: Obstructive sleep apnea (OSA) is known to be associated with diabetes mellitus (DM). Age is factor associated with different clinical features of OSA. There is limited data on clinical differences of young DM patients with OSA versus older DM patients with OSA. This study aimed to find clinical differences of DM coexisting with OSA between young age group and older. Methods: This is a retrospective, analytical study conducted at Srinagarind Hospital, Thailand. The inclusion criteria were adult patients diagnosed as DM with OSA. The study period was between January 2008 and December 2019. The diagnosis of OSA was made by presence of apnea hypopnea index (AHI) of ≥5 times/hour by polysomnography. Clinical predictors of OSA in young DM patients with age under 40 years were executed. Results: There were 56 patients in the young diabetes mellitus group, while there were 137 patients in the older diabetes mellitus group. The mean (SD) age of diagnosis for diabetes mellitus of both groups were 31.61 (6.53) and 54.68 (7.62) years, respectively. There were three independent predictors for DM in the young: atrial fibrillation (AF), body mass index (BMI) and glomerular filtration rate (GFR). Presence of AF perfectly predicted DM with OSA in age over 40 years. The adjusted odds ratio for BMI and GFR were 1.29 (95% CI 1.05, 1.58) and 1.06 (1.01, 1.13). The BMI over 32 kg/m 2 and GFR over 77 ml/min/m 2 gave sensitivity of 80.00%. Conclusions: Young DM patients with OSA had more severe OSA, were more obese, had better renal function, and had fewer AF than the older ones. Highlights: Obstructive sleep apnea (OSA) is associated with diabetes mellitus (DM). OSA coexisting with DM is commonly found in individuals with age of over 40 years. Young DM patients with OSA had more severe OSA. Renal function and atrial fibrillation were different factors between young and older DM with OSA.